Ocellus-bearing Neobythites species (Teleostei: Ophidiidae) from the West Atlantic with description of a new species - Nielsen, Jørgen G.; Uiblein, Franz; Mincarone, Michael M. (Zootaxa, 2009)
Three species of the ophidiid genus Neobythites containing ocelli in the dorsal fin are known from the West Atlantic: Neobythites gilli Goode and Bean 1885, N. ocellatus Günther 1887 and N. monocellatus Nielsen 1999. In the year 2000, 18 specimens of Neobythites were caught on the upper continental slope off eastern Brazil. This is the first documented record of a Neobythites specimen off Brazil since the holotype of N. ocellatus was caught in 1873. Seventeen of the specimens are referable to N. ocellatus and one to N. monocellatus. Until now the distribution of N. ocellatus was considered to be from off Atlantic Florida, the Caribbean Sea and then a gap of 4500 km to the type locality off Brazil. However, the holotype and the 17 specimens differ from the more northerly recorded specimens in pattern and number of spots and ocelli on the dorsal fin. The 18 Brazilian specimens have two distinct ocelli, one near the origin of the dorsal fin and one above the midpoint of the fish, and further back occasionally a small, black spot, while the northern specimens occasionally have a small, black spot near the origin of the fin, a distinct ocellus above the midpoint and up to three ocelli further posteriorly. Consequently a new species, N. multiocellatus, is described based on 59 specimens from the Caribbean Sea to off Atlantic Florida. The record of the N. monocellatus specimen extends its distribution about 3000 km southwards. A comparison of the four ocellus-bearing species from the West Atlantic is made.